Implementation of Guided Inquiry Model in Improving Problem Solving Skills and Student Activity at SD Negeri 01 Bulusari - Turiyah Turiyah (Universitas Sebelas Maret, 2019)
This study aims to determine the improvement of problem-solving skills and student activity in grade 3 by using the guided inquiry model. This research is a classroom action research with 22 students as the research subjects. This study consisted of 2 cycles that each cycle has 2 times of meetings. The utilized instruments were test sheet, interview sheet, and observation sheet. The data analysis technique uses descriptive qualitative. The results of the analysis show that: 1) the guided inquiry model can improve problem solving skills and student activity that achieved a good category; 2) The average value of students' problem solving skills in the first cycle was 52,49 with completeness of 40,90% while in the second cycle of 81,81 with completeness of 93,17%; 3) The average activity score of students in the first cycle was 23,16 while in the second cycle was 33,06.